Minilaparatomy for repair of ruptured abdominal aortic aneurysm - Klokočovnik, Tomislav (Endoskopska revija, 2006)
We report on a 56-year-old patient with ruptured abdominal aortic aneurysm (RAAA). Endoaneurysmography using the minilaparotomy approach was used to reduce surgical trauma due to intraoperative bowel manipulation, and to prevent postoperative adynamic ileus that prolongs postoperative recovery. Thepatient's postoperative course was uneventful and he was discharged home outhe 3rd postoperative day.
Keywords: Aorta, ruptura; Aortic Aneurysm, Abdominal; Aortna anevrizma trebušna; Surgery; Laparotomija; Aortic Rupture; Laparotomy; Srednja leta; Middle Age; anevrizma; abdominalna aorta; kirurško zdravljenje